2004
DOI: 10.1139/h04-035
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Physiology and Responses of Ultramarathon Athletes to Prolonged Exercise

Abstract: The purpose of this study was to determine the changes of pulmonary function and autonomic cardiovascular control after an ultramarathon and their relation to performance. Eight entrants to the Canadian National Championship 100-km running race participated in the study. Pulmonary function and 30-s maximum voluntary ventilation (MVV30s) tests were conducted one day before the race and within 5 minutes of race completion. Heart rate and blood pressure data were collected 30 min before and 5 min after the race a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 57 publications
2
11
0
2
Order By: Relevance
“…In line with studies from Hill et al, 3 Blaber et al, 4 and Zarvorsky et al, 24 we found significant reductions in all lung function variables after the race (Table 2). Blaber et al 4 observed that FEV 1 /FVC, MVV 30s , and MVV 30s TV were reduced from baseline to after an ultra‐marathon in eight runners and Hill et al 3 reported declines in FVC (7.1%), FEV 1 (8.4%), and FEF 50 (18.6%), but not in MVV in 12 participants after a long‐distance triathlon.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with studies from Hill et al, 3 Blaber et al, 4 and Zarvorsky et al, 24 we found significant reductions in all lung function variables after the race (Table 2). Blaber et al 4 observed that FEV 1 /FVC, MVV 30s , and MVV 30s TV were reduced from baseline to after an ultra‐marathon in eight runners and Hill et al 3 reported declines in FVC (7.1%), FEV 1 (8.4%), and FEF 50 (18.6%), but not in MVV in 12 participants after a long‐distance triathlon.…”
Section: Discussionsupporting
confidence: 92%
“…The day after the race, 28% still had obstructive features with a reduction in FEV 1 ≥ 10%. This is in line with previous studies in triathletes 3,8,10,16,38 as well as in marathon and ultra‐marathon runners 4,7 . However, the sample size is small in most studies and the included athletes are often at elite level 3‐4,7‐8,10 .…”
Section: Perspectivessupporting
confidence: 89%
See 1 more Smart Citation
“…4,8 Respiratory muscle fatigue could explain the diminished flow rates observed and has been documented after exercise if the intensity level is high or the duration is prolonged to exhaustion. 3,7,8 The further decline of FVC and FEV 1.0 on day 3 could be due to both performing the more cardiorespiratory-demanding 85-km run to near exhaustion on day 3 and the cumulative effects of 3 days of fatiguing competition. Respiratory muscle fatigue induced before high-intensity exercise has been shown to reduce subsequent performance.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been well accepted that aerobic fitness is highly dependent on cardiorespiratory system [17], several studies have also found a strong association between muscle strength and aerobic fitness [18,19]. Individuals with greater muscle strength could generate lower relative force at the same absolute running intensity.…”
Section: Introductionmentioning
confidence: 99%